Allocation of liver grafts worldwide – Is there a best system? - Tschuor, Christoph; Ferrarese, Alberto; Kuemmerli, Christoph; Dutkowski, Philipp; Burra, Patrizia; Clavien, Pierre-Alain; Lendoire, Javier; Imventarza, Oscar; Crawford, Michael; Andraus, Wellington; D'Albuquerque, Luiz Augusto Carneiro; Hernandez-Alejandro, Roberto; et al. (Journal of hepatology, 2019)
[Display omitted] •An optimal allocation system for scarce resources should simultaneously ensure maximal utility, but also equity.•Large differences exist between centers and countries for ethical and legislative reasons.•A future globally applicable strategy should combine donor and recipient factors.•This strategy must predict probability of death on the waiting list, post-transplant survival and morbidity, and costs. An optimal allocation system for scarce resources should simultaneously ensure maximal utility, but also equity. The most frequent principles for allocation policies in liver transplantation are therefore criteria that rely on pre-transplant survival (sickest first policy), post-transplant survival (utility), or on their combination (benefit). However, large differences exist between centers and countries for ethical and legislative reasons. The aim of this study was to report the current worldwide practice of liver graft allocation and discuss respective advantages and disadvantages. Countries around the world that perform 95 or more deceased donor liver transplantations per year were analyzed for donation and allocation policies, as well as recipient characteristics. Most countries use the model for end-stage liver disease (MELD) score, or variations of it, for organ allocation, while some countries opt for center-based allocation systems based on their specific requirements, and some countries combine both a MELD and center-based approach. Both the MELD and center-specific allocation systems have inherent limitations. For example, most countries or allocation systems address the limitations of the MELD system by adding extra points to recipient’s laboratory scores based on clinical information. It is also clear from this study that cancer, as an indication for liver transplantation, requires special attention. The sickest first policy is the most reasonable basis for the allocation of liver grafts. While MELD is currently the standard for this model, many adjustments were implemented in most countries. A future globally applicable strategy should combine donor and recipient factors, predicting probability of death on the waiting list, post-transplant survival and morbidity, and perhaps costs. An optimal allocation system for scarce resources should simultaneously ensure maximal utility, but also equity. While the model for end-stage liver disease is currently the standard for this model, many adjustments were implemented in most countries. A future globally applicable strategy should combine donor and recipient factors predicting probability of death on the waiting list, post-transplant survival and morbidity, and perhaps costs.